Um estudo sobre fatores humanos com foco em acidentes e incidentes aéreos - Bueno, Marina Ribeiro (2018)
This paper deals with the subject of human factors within the aeronautical industry, considering that errors caused in this segment can cause irreparable losses. The causes for these errors are broad, being studied by multidisciplinary areas. The objective of this study is to analyze the human factors as a critical point for accidents and aerial incidents. For that, a survey of these factors was made, in order to identify and study them, from the technical point of view of aeronautical legislation. The approach was done through a method known as SHELLO model, in order to investigate the most frequent risks that the organization may suffer. This model allows us to analyze the risks that most cause human errors in aircraft maintenance. Reaching a positive and satisfactory result, with the analysis of man, machine and its limitations.